Pengaruh Pengembangan Karir, Gaji, Dan Beban Kerja Terhadap Kinerja Karyawan Staff Office PT. Cosmoprof Indokarya Banjarnegara - Yugi Hartati; Anis Turmudhi; Rahmania Mustahidda (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2024)
This study aims to determine the effect of career development, salary, and workload on the performance of PT. Cosmoprof Indokarya Banjarnegara. The sample in this study were employees of the Office Staff of PT. Cosmoprof Indokarya Banjarnegara. This study uses multiple linear regression and the sample used is a total of people. The results of this study Career development has a positive and significant effect, salary has a negative and significant effect, and workload has a positive and significant effect.